Experience of LGBTQIA2S+ populations with gambling during the COVID-19 pandemic: protocol for a mixed-methods study. Issue 2 (8th February 2023) - Brodeur, Magaly; Roberge, Pasquale; Cotton, Julie-Christine; Monson, Eva; Morvannou, Adele; Poitras, Marie-Eve; Lacasse, Anaïs; Jutras-Aswad, Didier; Couturier, Yves; Loignon, Christine; Audette-Chapdelaine, Sophie; Auger, Anne-Marie; et al.
Abstract : Introduction: Research undertaken since the beginning of the COVID-19 pandemic has provided us information about the impact of the pandemic on the gambling habits of the general population. However, very little is known about certain subgroups at increased risk of developing gambling disorder, such as the LGBTQIA2S+ population. The purpose of this study is to describe the impact of the COVID-19 pandemic on gambling behaviours among LGBTQIA2S+ individuals. In addition, we want to understand the experiences of the LGBTQIA2S+ population with gambling disorder and identify interventions that LGBTQIA2S+ people have found to be effective in addressing problem gambling during the COVID-19 pandemic. Methods and analysis: This study has a sequential explanatory mixed-method design in two phases over 2 years. The first phase is a correlational study. We will conduct a cross-sectional survey using a stratified random sampling among Canadian residents who are 18 years of age or older, self-identify as sexually and gender-diverse (ie, LGBTQIA2S+) and have gambled at least once in the previous 12 months. This survey will be administered online via a web panel (n=1500). The second phase is a qualitative study. Semistructured interviews will be conducted with LGBTQIA2S+ people with problematic gambling (n=30). Ethics and dissemination: This research project has been ethically and scientifically approved by the Research Ethics Committee and by the CIUSSS de l'Estrie—CHUS scientific evaluation committee on 3 March 2022 (reference number: 2022-4633—LGBTQ-JHA). Electronic and/or written informed consent, depending on the data collection format (online survey and online or in-person interviews), will be obtained from each participant. A copy of the consent form and contact information will be delivered to each participant.